2020
DOI: 10.1155/2020/4928905
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Repeated Intravitreal Ranibizumab and Aflibercept Injections on the Cornea in Patients with Age-Related Macular Degeneration

Abstract: Purpose. To assess the effect of repeated intravitreal ranibizumab injections (RI) and aflibercept injections (AI) on the corneal endothelium and central corneal thickness (CCT) in patients with age-related macular degeneration (AMD). Materials and Methods. In the retrospective study, 110 eyes of 106 patients, aged 52 to 93 years, were analyzed. Fifty eyes were treated only with RI (I group), and 60 eyes were treated only with AI (II group). Every patient received one intravitreal injection of 0.5 mg of ranibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…However, additional clinical data is still needed to study the long-term risk because anti-VEGF agents are in direct contact with the corneal endothelium. 84 …”
Section: Limitations Of Anti-vegf Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…However, additional clinical data is still needed to study the long-term risk because anti-VEGF agents are in direct contact with the corneal endothelium. 84 …”
Section: Limitations Of Anti-vegf Therapymentioning
confidence: 99%
“…However, additional clinical data is still needed to study the long-term risk because anti-VEGF agents are in direct contact with the corneal endothelium. 84 Studies have found that LMSCs have the potential to treat corneal injuries, and repeated intravitreal injection of anti-VEGF drugs may reduce LMSC reserves due to their toxic effects. There is a case report of a patient who developed iatrogenic limbal stem cell deficiency due to the intravitreal injection of bevacizumab seven times, indicating that repeated surgical trauma to the limbus and surrounding areas may damage the LMSCs.…”
Section: Corneal Endothelial Injury and Limbal Mesenchymal Stem Cell ...mentioning
confidence: 99%
“…For instance, Merz et al [6] found that Ranibizumab and Bevacizumab were not toxic to corneal endothelial cells under in vitro experimental conditions. However, Beata et al [7] performed a retrospective study on patients with nAMD and discovered that Aflibercept and Ranibizumab could significantly reduce the corneal endothelial cell density (ECD), additionally, the proportion of hexagonal cells (Hex%) and CV also changed to a certain extent. Most of the above reports are retrospective in nature, and most of the literature reports are observations made following the administration of a particular drug for a specific disease.…”
Section: Introductionmentioning
confidence: 99%